(untitled) (Historia, 2021)
It is an honour to have been asked to make a few remarks at the end of the South African Historical Association Conference “Heritage Creation and Research: The Restructuring of Historical Studies in South Africa”,organised by Grietjie Verhoef and her team at RAU. Conferences themselves are part of the academic and social heritage and they have identifiable components without which the tradition would be incomplete.